IRRIGATION AND ENERGY: ISSUES AND CHALLENGES. (26th April 2019) - Belaud, G.; Mateos, L.; Aliod, R.; Buisson, M.‐C.; Faci, E.; Gendre, S.; Ghinassi, G.; Gonzales Perea, R.; Lejars, C.; Maruejols, F.; Zapata, N.
Abstract: Water‐efficient agriculture has implied a large increase in energy consumption for irrigation in recent decades. In many irrigation systems, energy costs are now threatening their sustainability. However, new opportunities have arisen for the use of renewable energies in the irrigation sector. These are some of the aspects of the multifaceted multiple‐actor 'water–food–energy' nexus. Technical, economic and environmental issues are linked in many ways, involving farmers, water users' associations, energy suppliers, engineers and other stakeholders. The ICID session 'Irrigation and energy' triggered discussions on these multiple dimensions. This paper presents a synthesis of the presentations, discussions and conclusions. Four main questions are addressed: How do irrigation productivity and sustainability of water resources exploitation change when farmers have access to energy? What do we know about energy efficiency in irrigation systems, at farm and collective network levels? How can this efficiency be optimized by using advanced technologies, modelling tools, improved management? Is energy production an opportunity for irrigation systems? These questions have been posed based on multiple case studies from different parts of the world. The BRL network, in southern France, illustrates advanced strategies and opportunities to reduce energy consumption and develop energy production at a network level. General conclusions are drawn from this synthesis, illustrating trade‐offs and synergies that can be identified in the irrigation sector at different scales, while opportunities for future research are proposed. © 2019 John Wiley & Sons, Ltd. Résumé: L'agriculture économe en eau a entraîné une forte augmentation de la consommation d'énergie pour l'irrigation au cours des dernières décennies. Dans de nombreux systèmes d'irrigation, les coûts énergétiques menacent maintenant leur durabilité. Cependant, de nouvelles opportunités sont apparues avec l'utilisation des énergies renouvelables dans le secteur de l'irrigation. Ce sont quelques‐uns des aspects du nexus 'eau–alimentation–énergie'. Les problèmes techniques, économiques et environnementaux sont liés à bien des égards, impliquant les agriculteurs, les associations d'usagers de l'eau, les fournisseurs d'énergie, les ingénieurs et d'autres parties prenantes. La session CIID 'Irrigation et énergie' a ouvert le débat sur ces multiples dimensions. Ce document présente une synthèse des présentations, discussions et conclusions. Quatre questions principales sont abordées: Comment la productivité de l'irrigation et la durabilité de l'exploitation des ressources en eau changent‐elles lorsque les agriculteurs ont accès à l'énergie? Que savons‐nous de l'efficience énergétique dans les systèmes d'irrigation, au niveau de l'exploitation et des réseaux collectifs? Comment optimiser cette efficience en utilisant des technologies avancées, des outils de modélisation, une gestion améliorée? La production d'énergie est‐elle une opportunité pour les systèmes d'irrigation? Ces questions ont été posées à partir de multiples études de cas provenant de différentes régions du monde. Le réseau BRL, situé dans le sud de la France, illustre les stratégies avancées et les possibilités de réduction de la consommation d'énergie et de développement de la production d'énergie au niveau du réseau. Des conclusions générales sont tirées de cette synthèse, illustrant des compromis et des synergies pouvant être identifiés dans le secteur de l'irrigation à différentes échelles, tandis que des opportunités de recherche future sont proposées. © 2019 John Wiley & Sons, Ltd.